Responsivitas Pelayanan Pengelolaan Sampah di Dinas Pertamanan dan Kebersihan Kota Makassar - Kasriana, Kasriana; Fatmawati, Fatmawati; Haerana, Haerana (Universitas Muhammadiyah Makassar, 2020)
This study purposed to determine the responsiveness of waste management service in the Makassar City parks and Sanitation Department. This study used descriptive research with a qualitative appoarch. Data collection techniques were interview, observation and documentation. Data analisys used data reduction, data presentation and conclusions, while the validity of the data used triangulation of sources, techniques and time. The results of the study showed that the level of government responsiveness in waste management service in the Makassar City Sanitation and Sanitation Service was measured in four dimensions: speed of service, accuracy of service, precision of service and abilityto respond to complaints that were still low in meeting the needs of the community such as providing facilities and infrastructure and improvement of waste transportation schedules that had not been fully met.